In Vitro Anti-Shigella, Antioxidant Activities, and Oral Acute Toxicity of Organics Extracts from the Root Bark of Detarium microcarpum Guill. and Perr. - Hama Hamadou Habibou; Mahamane Idi Issa Abdoulahi; Ikhiri Khalid (Journal of Tropical Medicine)
Detarium microcarpum (Fabaceae) is a medicinal plant from the traditional pharmacopeia of Niger used against gastrointestinal disorders and dysentery. This study was designed to assess the in vitro anti-shigella, antioxidant activities, and oral acute toxicity of extract root barks of Detarium microcarpum. The crude extracts were prepared by maceration using methanol, ethanol, dichloromethane, water-ethanol (30/70 v/v), and methanol-dichloromethane (1/1 v/v). The anti-shigella activity was performed using the microdilution method coupled with the resazurin-based assay. The antioxidant activity was evaluated by the DPPH· (2, 2-diphényl-1-picrylhydrazyl), ABTS 2, 2′-azino-bis (3-ethylbenzothiazoline-6-sulfonic acid), and H2O2 assays. The oral acute toxicity was assessed following the Organization for Economic Cooperation and Development (OECD) guidelines. The extracts displayed activity against the Shigella boydii with Minimum Inhibitory Concentrations (MICs) from 500 to 1000 μg/mL. The methanolic crude extract of D. microcarpum shows good antioxidant activity with the radicals DPPH· and ABTS with inhibitory concentration 50 (IC50) at 228 and 191 µg/mL, respectively. The lethal dose 50 (LD50) of extract was up to 2000 mg/kg of body weight, and no signs of toxicity were observed. These findings supported the use of Detarium microcarpum in the traditional treatment of gastrointestinal disorders.